APLIKASI “SIPELAPOR” UNTUK PENGOLAHAN NILAI RAPOR PADA SMP NEGERI 26 PURWOREJO - Eka Yulistia Nurwanti; Anastasia Meyliana (SPEED - Sentra Penelitian Engineering dan Edukasi, 2019)
Abstract -  The education process is inseparable from teaching and learning activities in the classroom. One of the tools that can be used to measure and evaluate the results of KBM is report card grades. At SMP Negeri 26 Purworejo report processing still requires a long time because the process is done manually. Therefore, the purpose of making the "reporter" application is to facilitate the school in processing values so as to speed up student report card information. In designing the system several data collection techniques are used such as observation, interviews and literature. Meanwhile, the method of software development used is Rapid Application Development (RAD). The design stage uses the PHP and HTML programming languages, while the database uses MySQL. To find out the system functionality of the application that has been built using the Blackbox testing test method. The results of unit testing show that the application of the "reporter" runs well as expected and the calculation of values becomes faster because it is done automatically by the system. Keyword: rapid application development, report, grade, blackbox